What Shifts Epistemic Standards? DeRose on Contextualism, Safety, and Sensitivity - Blome-Tillmann, Michael (International journal for the study of skepticism, 2020)
In The Appearance of Ignorance, Keith DeRose develops a version of epistemic contextualism that combines aspects of both safety and sensitivity theories of knowledge. This paper discusses some potential problems for DeRose's account stemming from his Rule of Sensitivity, which is meant to model upwards shifts in epistemic standards.